2006
DOI: 10.1103/physreve.73.041510
|View full text |Cite
|
Sign up to set email alerts
|

Ultraslow dielectric relaxation process in supercooled polyhydric alcohols

Abstract: Complex permittivity was obtained on glycerol, xylitol, sorbitol and sorbitol-xylitol mixtures in the supercooled liquid state in the frequency range between 10 microHz and 500 MHz at temperatures near and above the glass transition temperature. For all the materials, a dielectric relaxation process was observed in addition to the well-known structural alpha and Johari-Goldstein beta relaxation process [G. P. Johari and M. Goldstein, J. Chem. Phys. 53, 2372 (1970)]. The relaxation time for the new process is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…It is seen that we are definitely observing the same process. Our observation thus confirms the observation by Yomogida et al 21 without resorting to such a difficult subtraction of conductivity from the data. However, in contrast to that study, where it was found that the dielectric strength of the "ultraslow process" decreases with time, we found an almost time independent amplitude of the Debye-like process.…”
Section: -3supporting
confidence: 82%
See 2 more Smart Citations
“…It is seen that we are definitely observing the same process. Our observation thus confirms the observation by Yomogida et al 21 without resorting to such a difficult subtraction of conductivity from the data. However, in contrast to that study, where it was found that the dielectric strength of the "ultraslow process" decreases with time, we found an almost time independent amplitude of the Debye-like process.…”
Section: -3supporting
confidence: 82%
“…However, these types of subtractions are difficult as one essentially subtracts a huge conductivity contribution to extract a rather small feature in the spectra. The data of Yomigida et al 21 obtained by time domain dielectric spectroscopy and ours are complementary also regarding the covered frequency windows and their obtained peak relaxation times are compared to our data in Fig. 3.…”
Section: -3mentioning
confidence: 72%
See 1 more Smart Citation
“…This, together with the agreement with complementary data by Yomogida et al 3 make us confident that the main conclusions of the original article 2 are right.…”
supporting
confidence: 76%
“…2) or by carefully subtracting the right conductivity contribution in the imaginary part. It should also be noted that not only the present reply and the previous articles 2, 3 on polyalcohols show that the statement 5 that the Debye-like relaxation only exists in monoalcohols is wrong. Recently, a slow Debye-like relaxation has also been observed in water-glycerol mixtures 6 and monosaccharides, 7 proving that this ultraslow process is The dashed line shows the α-relaxation, the dotted line the Debye-like process, and the solid line the resulting total fit using the conductivity obtained from (a), which is indicated by the dashed-dotted line.…”
mentioning
confidence: 76%